Work Integrated Learning (WIL) Good Practice Case Studies. - Sachs, Judyth; Rowe, Anna; Wilson, Michael (Dept of Education and Training, Australia, 2016)
The Australian Government Office for Learning and Teaching commissioned a report to identify good practices in work-integrated learning (WIL) in Australian universities through a systematic review of current approaches in universities in Australia and elsewhere. This report takes up where Janice Orrell's 2011 benchmark report left off and provides contemporary case studies of good practice evident in 13 Australian universities and from two overseas universities.